Impact evaluation of the use of PBR cowpea in Nigeria: Baseline report - Andam, Kwaw S.; Amare, Mulubrhan; Zambrano, Patricia; Bamiwuye, Temilolu; Nwagboso, Chibuzo; Fasoranti, Adetunji; Edeh, Hyacinth O.; Chambers, Judith A. (International Food Policy Research Institute, 2024)
Nigeria is the largest consumer and producer of cowpea in Africa. Produced predominantly by smallholder farmers, cowpea is relied on by millions of Nigerians and is one of their main sources of affordable protein. Despite cowpea’s economic relevance (Nwagboso et al. 2024; Phillip et al. 2019), cowpea yields in Nigeria have barely grown over the last 20 years. One of the main abiotic constraints of the crop is the pod-borer insect (Maruca vitrata), which can cause damages of up to 80 percent. Given that conventional breeding has not been successful in addressing this constraint, local and international efforts over the last decades focused on developing a pod-borer-resistant (PBR) cowpea. The culmination of these efforts in Nigeria was the commercial release of the PBR cowpea variety SAMPEA-20T in late 2019. This is a significant milestone, as it was the first transgenic food crop to be approved for cultivation in Nigeria. In its programming under the “Feed the Future Innovative Maize and Cowpea Technologies to Increase Food and Nutrition Security in Africa” activity, implemented by the African Agricultural Technology Foundation (AATF), the United States Agency for International Development (USAID) aims for an adoption rate of PBR cowpea in Nigeria of 25 percent by 2025, with yield gains of 20 percent and accompanying reductions in pesticide applications. The International Food Policy Research Institute’s (IFPRI) Program for Biosafety Systems (PBS) is leading a five-year (2021–2026) impact evaluation (IE) project, funded by USAID. The study goal is to generate causal evidence of the use of the PBR cowpea variety and its consequential household and farm impacts and associated value chain effects. In a collaboration with IFPRI’s Nigeria Country Office, PBS is leading and coordinating the overall study while the IFPRI-Nigeria Country Office designs and implements the quantitative and qualitative approaches to the evaluation. IFPRI has worked with technology developers, the AATF and its partners (including private local seed companies), to ensure access to necessary data and cooperation by the evaluation team, while maintaining the team’s independence. To ensure such required independence, the evaluation team has separated the cooperation in implementing the evaluation (including distributing inputs) from the data analysis. The evaluation team will continue to maintain its independence in the methodological approach and the analysis of the results from the implemented randomized controlled trial (RCT), adhering to international standards.